Prevalence and Determinants of Choice Bracketing - Experimental Evidence - Rudi Stracke; Rudolf Kerschbamer; Uwe Sunde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates whether the timing of rewards affects behavior in multi-stage contests. Abstracting from discounting, theory predicts that it is irrelevant for behavior whether agents are immediately rewarded for succeeding on a particular stage, or whether the reward is delayed until the interaction on the subsequent stage is decided. When testing this prediction using a two-stage contest in lab experiments, we fnd that stage-2 efforts are identical in immediate and delayed reward treatments, while stage-1 effort is significantly lower if rewards are immediate. This difference can be explained by the salience of continuation values, which is strongly affected by the timing of rewards.
Keywords: C72; M52; J33; 330